Identification of Groundwater Aquifers Using 2D Resitivity Imaging Technique in South Parigi Sub-District, Indonesia - Muhammad Rusydi, Moh. Dahlan Th. Musa, Badaruddin, Rosida Y.Saada, Sandra, Rahmawati, Rosmala Nur (International Journal of Advanced Science and Technology, 2020)
The supply of clean water in the South Parigi District, Sulawesi, Indonesia, is managed by the Regional Water Company, but the discharge is very small so that the distribution to the community is carried out in rotation to meet the needs of clean water. For this reason, it is necessary to find other clean water sources, one of which comes from groundwater. The purpose of the study is to determine the distribution of aquifer layers in the South Parigi District. This is a survey research using the geoelectric resistivity method. The result was interpreted with resistivity values ranging from 54 Ωm - 133 Ωm consisting of sand, gravel, sandstone, which has formation factor values of 2-5. The aquifer layers were detected spreading in varying depths between ± 5 m to ± 45 m below the surface with the most direction of aquifer layer distribution is in the middle part of the study area, the data comes from water wall data. This can be seen from the thickness of aquifer layers in Line 04, Line 05, and Line 06, which is greater than the other lines. The distribution of aquifer layers in the South Parigi District is in alluvium and coastal sediment formations.